Speech acts, mind, and social reality: discussions with John R. Searle - Grewendorf, Günther; Meggle, Georg (Springer, 2002)
Speech Acts, Mind, and Social Reality - these are the main topics in the work of John R. Searle, one of the leading philosophical figures of the present times. How language is based on intentionality, how intentionality in turn is to be explicated by means of distinctions discovered in Speech Act Theory, and how language and intentionality are both related to social facts and institutions - these are questions to be tackled in this volume. The contributions result from discussions on and with John R. Searle, containing Searle's own latest views - including his seminal ideas on Rationality in Action. The collection provides a good basis for advanced seminar debates in Philosophy of Language, Philosophy of Mind, and Social Philosophy, and will also stimulate some further research on all of the three main topics